Choosing Appropriate Metrics to Evaluate Adverse Events in Safety Evaluation. (May 2015) - Zhou, Ying; Ke, Chunlei; Jiang, Qi; Shahin, Seta; Snapinn, Steven
Safety assessment and monitoring are critical throughout the life cycle of drug development. The evaluation of safety information, specifically adverse events, from clinical trials has always been challenging for a number of reasons, such as the unexpectedness and rarity of some important adverse events, the fact that some events can recur, and the events' variability in duration and severity. To accurately characterize and communicate the risk profile of a drug, the choice of metrics is critical. However, there seems to be a lack of consistency, clear guidance, and comprehensive recommendations on choosing metrics for assessing adverse events in clinical trials. This article reviews the common metrics and provides some recommendations.